Sexualidade no ambiente escolar: narrativas de adolescentes do ensino médio de uma escola da rede pública em Serra-ES - Madeira, Thiago Fernandes (2019)
Sexuality is a controversial issue in the school and family environment, and each of these social institutions has the responsibility to educate, inform and guide children and adolescents about the discoveries and changes that occur. There are several discourses about sexuality involving adolescence, but few are found from the perception of the subjects themselves, therefore, it was intended to bring out the feelings that are fed by them, as students and how this experience is processed. The theoretical framework had as its main source of information the theory of sexuality proposed by Sigmund Freud, analyzed by other theorists, aiming to identify the perception of high school adolescents about sexuality in the school environment, in the family, in religion. The methodology used was a case study with a qualitative approach, based on data description analysis of 12 students enrolled in high school of a state school in the municipality of Serra, Holy Esprit. Data were collected from focus group meetings to verify students' knowledge of the topic and to define the themes developed and discussed in open interviews with research subjects. From the themes defined in the focus groups, most adolescents showed to know about the importance of discussing sexuality issues at school and family, with firm, clear and objective opinions that the subject is not adequately addressed in these two spaces. And that there is a need to enable and qualify the teacher for the themes of sex and sexuality to be approached in the classroom and in a more natural way to open and maintain dialogue in the family.